1996
DOI: 10.1021/es950579e
|View full text |Cite
|
Sign up to set email alerts
|

Chlorine Input and Chlorophenol Emission in the Lab-Scale Combustion of Municipal Solid Waste

Abstract: Incineration of municipal solid waste (MSW) yields a variety of chlorinated aromatics such as chlorophenols. In this study, regular and modified samples of MSW have been processed in a micromodel reactor mimicking the primary combustion chamber of a practical MSW incinerator. To understand the relationships between the origin of chlorine in the feed and the formation of products of incomplete combustion (PICs) and HCl, emitted chlorophenols (CPs) and HCl have been measured. With humidified air as the carrier g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…For the Amsterdam MSW incineration plant TCC of 4.1 g/kg raw waste is reported (3.1 g/kg raw waste in stack emission, 0.4 g/kg in slag, 0.5 g/kg in fly ash, and 0.1 g/kg in fly dust) [22]. Based on the data presented here, plastics (Pl1, Pl2, Pl3 in total) contribute to one third of the TCC, and organic waste (Org1, Org2) contains approximately 50% of TCC.…”
Section: Chlorine Relevance In Msw/rdfmentioning
confidence: 99%
See 2 more Smart Citations
“…For the Amsterdam MSW incineration plant TCC of 4.1 g/kg raw waste is reported (3.1 g/kg raw waste in stack emission, 0.4 g/kg in slag, 0.5 g/kg in fly ash, and 0.1 g/kg in fly dust) [22]. Based on the data presented here, plastics (Pl1, Pl2, Pl3 in total) contribute to one third of the TCC, and organic waste (Org1, Org2) contains approximately 50% of TCC.…”
Section: Chlorine Relevance In Msw/rdfmentioning
confidence: 99%
“…Based on the data presented here, plastics (Pl1, Pl2, Pl3 in total) contribute to one third of the TCC, and organic waste (Org1, Org2) contains approximately 50% of TCC. Kanters et al [22] reported that ca. 50% of the chlorine load of regular MSW is due to inorganic chloride and ca.…”
Section: Chlorine Relevance In Msw/rdfmentioning
confidence: 99%
See 1 more Smart Citation
“…In most attempts to study the reaction system, the concentration of Cl in the solid fuel or the concentration of HCl in the gas phase has been the variable controlled and monitored. The concentration of HCl in the gas phase was found to be proportional to the quantity of chlorine added (as PVC) to the feed of both a lab furnace [129] and a 220 kg h −1 incinerator [63]. In the pilot incinerator at Umeå, no distinction was found [130] between the types of chlorine, i.e., organic (PVC) or inorganic (CaCl 2 ·6H 2 O) added to synthetic MSW.…”
Section: Chlorinementioning
confidence: 99%
“…The form of chlorine released during the pyrolysis of PVC has been investigated by Kanters et al [129]. Various amounts of PVC up to 5 wt% were added to a simulated MSW containing 0.46% of Cl, and incinerated batchwise under air at 850 • C. The quantity of chlorophenols released into the gas remained virtually constant at 3.3 µmol/kg of dry waste at all levels of PVC addition.…”
Section: Oxygenmentioning
confidence: 99%